CAPITAL MANAGEMENT: AN IMPORTANT PRODUCTION FACTOR IN INCREASING THE PRODUCTION OF BIRUN COFFEE BEANS, JAMBI - Iwil suprianto; Kurniasih setyagustina; Winahyu Dwi Suhitasari (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2023)
Capital is a very important factor in the smooth production. Coffee production produced by farmers is not always stable or increasing, coffee farmers will face problems with yields that will decrease or even fail to harvest, this will be caused by capital, weather, labor and so on. This study uses a quantitative approach and the type of research used in this study is field research using a questionnaire instrument in data collection. The researcher analyzed the data using a simple linear regression analysis tool and used the SPSS computer program to process the research data Hasil penelitian yang telah dilakukan mengenai Pengaruh modal terhadap peningkatan produksi biji kopi menunjukkan bahwa modal mempunyai pengaruh positif terhadap peningkatan produksi biji kopi di Desa Birun Kecamatan Pangkalan Jambu Kabupaten Merangin. It can be seen from the results of this study indicating that the greater the capital used by coffee farmers, the greater the increase in coffee bean production. so capital management must be carried out by coffee farmers, of course, cannot be separated from government support to provide education to farmers about capital management so that it is effective and efficient Keywords: Capital, coffee Production, coffee beans, coffee farmer